Binomially expand the equation (2+kx)^-3

(2+kx)-3 = (2-3)(1+kx/2)-3 = (2-3)(1+(-3)(kx/2) + [(-3)(-4)]/2! (kx/2)2 + [(-3)(-4)(-5)]/3! (kx/2)3 +... )
= 1⁄8 [1 -(3kx/2) + (12⁄2 k2x2/4) + (60⁄6 k3x3/8) + ...]
= 1⁄8 [1 - (3⁄2 kx) + ( 3⁄2 k2x2) + (5⁄4 k3x3) + ...]
= 1⁄8 - 3⁄16 kx + 3⁄16 k2x2 + 5⁄32 k3x3

Answered by Christopher H. Maths tutor

8033 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Differentiate y=x*ln(x^3-5)


f(x) = x^x, find f'(3).


differentiate x^2 + 7x + 4


How do you find the possible values of cos(x) from 5cos^2(x) - cos(x) = sin^2(x)?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences